Targeted deletion of MMP-9 attenuates myocardial contractile dysfunction in heart failure - Moshal, K S; Rodriguez, W E; Sen, U; Tyagi, S C (Physiological research, 2008)
Chronic volume overload (VO) on the left ventricle (LV) augments redox stress and activates matrix metalloproteinase (MMP) which causes the endocardial endothelial-myocyte (EM) disconnection leading to myocardial contractile dysfunction. VO-induced MMP-9 activation impairs cardiac functions, in part by endothelial endocardial apoptosis, but the role of MMP-9 on EM functions remains obscure. We conjecture that chronic VO activates MMP-9 and causes EM uncoupling. Arteriovenous fistula (AVF) was created in genetically identical wild type (WT) mice (FVB/NJ) and MMP-9 knockout mice (MMP-9KO, FVB.Cg-MMP9(tm1Tvu)/J). Sham-operated mice were used as controls. Before experimentation the phenotype analysis of MMP-9KO mice was carried out. In-gel-gelatin zymography for MMP-9 activation was performed on LV homogenates. The EM functions were determined on LV rings using tissue myobath. We report a decrease in MMP-9 activity in left ventricular myocardial extracts in MMP-9 deficient mice after AVF. The responses to drugs affecting cardiac functions (acetylcholine (Ach), nitroprusside and bradykinin) were attenuated in AVF mice suggesting the impairment of EM coupling. Interestingly, the EM functions were restored in the MMP-9 deficient mice after AVF. We suggest a direct cause-and-effect relationship between MMP-9 activation and EM uncoupling in LV myocardium after chronic VO and the possible involvement of MMP-9 in myocardial contractile performance.
Keywords: bradykinin; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Acetylcholine; Arteriovenous Shunt, Surgical; Myocardial Contraction; Bradykinin; acetylcholin; Disease Models, Animal; mužské pohlaví; Mice; srdeční komory; funkce levé komory srdeční; fenotyp; myši knockoutované; nitroprusid; Enzyme Activation; Matrix Metalloproteinase 9; Phenotype; modely nemocí na zvířatech; myokard; zvířata; Nitroprusside; Myocardium; endoteliální buňky; Heart Ventricles; srdeční selhání; aktivace enzymů; Mice, Knockout; myši; kontrakce myokardu; matrixová metaloproteinasa 9; arteriovenózní zkrat; Ventricular Function, Left; Heart Failure; Male; Endothelial Cells; Animals